Asthma symptoms and nasal congestion as independent risk factors for insomnia in a general population: results from the GA 2 LEN survey. Issue 2 (26th November 2012) - Sundbom, F.; Lindberg, E.; Bjerg, A.; Forsberg, B.; Franklin, K.; Gunnbjörnsdottir, M.; Middelveld, R.; Torén, K.; Janson, C.
Abstract Background Asthma and rhinitis have been related to insomnia. The aim of this study was to further analyse the association between asthma, nasal symptoms and insomnia and to identify risk factors for sleep disturbance among patients with asthma, in a large population‐based set of material. Method In 2008, a postal questionnaire was sent to a random sample of 45 000 adults in four Swedish cities. The questionnaire included questions on insomnia, asthma, rhinitis, weight, height, tobacco use and physical activity. Results Twenty‐five thousand six hundred and ten subjects participated. Asthma was defined as either current medication for asthma or at least one attack of asthma during the last 12 months, and 1830 subjects (7.15%) were defined as asthmatics. The prevalence of insomnia symptoms was significantly higher among asthmatics than non‐asthmatics (47.3% vs 37.2%, <0.0001). In the subgroup reporting both asthma and nasal congestion, 55.8% had insomnia symptoms compared with 35.3% in subjects without both asthma and nasal congestion. The risk of insomnia increased with the severity of asthma, and the adjusted OR for insomnia was 2.65 in asthmatics with three symptoms compared with asthmatics without symptoms. Nasal congestion (OR 1.50), obesity (OR 1.54) and smoking (OR 1.71) also increased the risk of insomnia. Conclusion Insomnia remains a common problem among asthmatics. Uncontrolled asthma and nasal congestion are important, treatable risk factors for insomnia. Lifestyle factors, such as smoking and obesity, are also risk factors for insomnia among asthmatics.